2022
DOI: 10.1038/s43856-022-00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of SARS-CoV-2-positivity from million-scale complete blood counts using machine learning

Abstract: Background The Complete Blood Count (CBC) is a commonly used low-cost test that measures white blood cells, red blood cells, and platelets in a person’s blood. It is a useful tool to support medical decisions, as intrinsic variations of each analyte bring relevant insights regarding potential diseases. In this study, we aimed at developing machine learning models for COVID-19 diagnosis through CBCs, unlocking the predictive power of non-linear relationships between multiple blood analytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We also demonstrate the necessity of maintaining a model as up-to-date as possible to allow any machine learning model to keep up with the different stages of a pandemic surge. Our model retains high-performance values across multiple evaluation scenarios and on simulations with varying prevalences of COVID-19, properly differentiating Sars-CoV-2 from other confounding viruses, thus demonstrating the robustness of our approach presented in our work [Zuin et al, 2022a].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We also demonstrate the necessity of maintaining a model as up-to-date as possible to allow any machine learning model to keep up with the different stages of a pandemic surge. Our model retains high-performance values across multiple evaluation scenarios and on simulations with varying prevalences of COVID-19, properly differentiating Sars-CoV-2 from other confounding viruses, thus demonstrating the robustness of our approach presented in our work [Zuin et al, 2022a].…”
Section: Discussionmentioning
confidence: 64%
“…These properties imply a partial ordering of the graph starting from the root node, which allows us to search it in an orderly manner. It has been shown that this modeling approach is effective for the task at hand [Zuin et al, 2021[Zuin et al, , 2022a. We can, for example, apply the A* algorithm [Hart et al, 1968] employing as heuristic the performance of the model represented by the feature set of a given vertex and the Jensen-Shannon distance to the predictions of the remaining Rashamon subgroups clusteroids.…”
Section: Searching For Optimal Constituentsmentioning
confidence: 99%
“…This process of enumerating models and selecting the best-performing one based on AUC continues, with one additional feature being incorporated at each step. The procedure halts once the improvement in AUC no longer exceeds its standard deviation, ensuring a balance between model complexity and performance 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, complete blood count and routine biochemical markers have been less represented in ML approaches, though reaching similar AUROC values in combination with clinical risk factors such as comorbidities [ 8 , 9 , 10 , 11 , 12 ]. Moreover, an ensemble of laboratory markers has been suggested even for COVID-19 diagnosis [ 13 , 14 , 15 , 16 ], but the efficacy of this approach seems limited to pandemics, as having an unacceptably high risk of false positives related to other infectious diseases [ 17 ]. However, the rapid prognosis of COVID-19 using routine markers such as complete blood count or C-reactive protein might be a cost-efficient solution for developing and least-developed countries in case of pandemics caused by other SARS-CoV-2 mutants.…”
Section: Introductionmentioning
confidence: 99%